1995
DOI: 10.1021/bi00047a013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Geometric Isomerism and Ligand Substitution in Bifunctional Dinuclear Platinum Complexes on Binding Properties and Conformational Changes in DNA

Abstract: The DNA binding profile of a series of dinuclear platinum complexes [{trans-PtCl-(L)2}2H2N(CH2)nNH2]2+ (L = NH3 or py; 1,1/t,t/NH3 and 1,1/t,t/py, respectively) and [{cis-PtCl-(NH3)2H2N(CH2)nNH2]2+ (1,1/c,c/NH3) was examined to compare the effects of geometrical isomerism and the presence of ligands other than NH3 in the coordination sphere. Steric effects, because of the geometry of the leaving groups cis to the diamine bridge or the presence of planar pyridine ligands, result in diminished binding to calf th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
0
3

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(122 citation statements)
references
References 28 publications
(70 reference statements)
4
115
0
3
Order By: Relevance
“…Multinuclear platinum complexes, containing two reactive platinum centers linked by a relatively long chain, were originally designed to form long-distance' DNA cross-links. 1,16 Indeed, the multinuclear complex BBR 3464 is able to form DNA lesions different from those induced by cisplatin and to elicit a cellular response different from that of cisplatin. 2 The results of our study clearly document that BBR 3464 exhibited unusual features that could underlie the completely different pattern of cellular response compared to cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Multinuclear platinum complexes, containing two reactive platinum centers linked by a relatively long chain, were originally designed to form long-distance' DNA cross-links. 1,16 Indeed, the multinuclear complex BBR 3464 is able to form DNA lesions different from those induced by cisplatin and to elicit a cellular response different from that of cisplatin. 2 The results of our study clearly document that BBR 3464 exhibited unusual features that could underlie the completely different pattern of cellular response compared to cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Seu espectro de ação é semelhante ao da cisplatina, excetuando-se talvez os sarcomas e os tumores trofoblásticos, para os quais parece ser menos eficaz [6][7][8][9] . Mais recentemente, tem-se desenvolvido complexos diméricos análogos à cisplatina mas, apesar de muito promissores, ainda estão em fase inicial de investigação 39 .…”
Section: Cisplatinaunclassified
“…Previous studies using other techniques have shown that 1,1/t,t compounds bind to DNA more readily than 1,1/c,c compounds [5] and the first objective of the current study was to compare the kinetics of the stepwise formation of 1,4-interstrand cross-links by the geometric isomers 1,1/c,c and 1,1/t,t. Therefore, the initial reactions of 1 with duplex I were carried out under similar conditions to those employed in our previous study of 1,1/t,t in the presence of 15 mM phosphate buffer and with the chosen pH approximately 0.2 pH units below the pK a value of the diaquated species.…”
Section: Kinetics Of Formation Of the 14-interstrand Cross-linkmentioning
confidence: 99%
“…[1][2][3][4][5][6] This class includes the trinuclear [{trans-PtCl-(NH 3 ) 2 } 2 (μ-trans-Pt(NH 3 ) 2 {NH 2 (CH 2 ) n NH 2 } 2 )] 4+ (1,0,1/t,t,t, n=6, or BBR3464), which has undergone Phase II clinical trials (summarized in refs [1,[7][8][9]). The overall charge as well as the linker flexibility and hydrogen-bonding capability of these compounds are thought to be related to their improved cytotoxic and antitumor properties relative to cisplatin and its derivatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation